Victoria Theatre virtual reality: A digital heritage case study and user experience design. (June 2021) - Arrighi, Gillian; See, Zi Siang; Jones, Donovan
Abstract: This research study centres on a digital reconstruction of the heritage building, Victoria Theatre in Newcastle, Australia. The Virtual Reality project is called 'Visualising the Victoria.' The research focuses specifically on the on-going development and user experience aspects of using a transmedia virtual reality approach to preserving the heritage of this site. Traditional room-scale VR locomotion with 6 degrees of freedom relies heavily on 'teleport-style' method for users moving around the virtual space. However, this can be physically and mentally challenging for some new VR users and users with limited mobility. To explore different options, we seek for various interaction design alternatives and customisation that might work alongside the teleport-style method for improved perceived ease-of-use and usefulness of the VR system. A user experience study is included in this article. The focus of this usability pilot study is to provide an on-going understanding of feasible interaction design approaches to be included in digital heritage VR projects. In this paper we describe the case study, prototype, a user evaluation study and directions for future work.